Interministerial structuring actions for reorientation of Primary Health Care: convergence between education and humanization - Ferraz, Fabiane; Vendruscolo, Carine; Kleba, Maria Elisabeth; do Prado, Marta Lenise; Schmidt Reibnitz, Kenya (O Mundo da Saúde, 2012)
The Unified Health System (UHS) has among its prerogatives the organization of ways for training human resources for health. To meet this commitment, the Ministries of Health and Education have “structural inter actions” to promote the reorientation of professional practices through training and development strategies of health professionals in line with the UHS principles and guidelines. Among the initiatives we highlight: the National program of reorientation of professional training in health, the in-service Educational program for health, UHS Open University and Telessaude Brazil (distance health assistance). This paper proposes a reflection on the importance of the interrelationship between the theoretical and methodological principles of the Education Policy for Permanent Education in Health and Humanization as a way for structuring proposals relating to the aforementioned interministerial actions and their contribution in the preparation of professionals to carry out the Primary Health Care (PHC) in order to promote health. For this, we reflect on the origins and development of training and humanization, guided by the understanding that the actors must mobilize changes in and for the work process which promote the restructuring of the curriculum in order to produce similarities between teaching and service. We conclude that interministerial devices are strategies that encourage the participation of managers, employees, users and teaching institutions for promoting changes that may impact on the consolidation of an integral, humanized and effective public health system, but emphasize the need for changes in the social and political sectors for this to be effective.